Inhibition of Rho Kinase Regulates Specification of Early Differentiation Events in P19 Embryonal Carcinoma Stem Cells - Krawetz, Roman J.; Taiani, Jaymi; Greene, Alexis; Kelly, Gregory M.; Rancourt, Derrick E. (PLOS ONE, 2011)
Background The Rho kinase pathway plays a key role in many early cell/tissue determination events that take place in embryogenesis. Rho and its downstream effector Rho kinase (ROCK) play pivotal roles in cell migration, apoptosis (membrane blebbing), cell proliferation/cell cycle, cell-cell adhesion and gene regulation. We and others have previously demonstrated that inhibition of ROCK blocks endoderm differentiation in embryonal carcinoma stem cells, however, the effect of ROCK inhibition on mesoderm and ectoderm specification has not been fully examined. In this study, the role of ROCK within the specification and differentiation of all three germ layers was examined. Methodology/Principal Findings P19 cells were treated with the specific ROCK inhibitor Y-27623, and increase in differentiation efficiency into neuro-ectodermal and mesodermal lineages was observed. However, as expected a dramatic decrease in early endodermal markers was observed when ROCK was inhibited. Interestingly, within these ROCK-inhibited RA treated cultures, increased levels of mesodermal or ectodermal markers were not observed, instead it was found that the pluripotent markers SSEA-1 and Oct-4 remained up-regulated similar to that seen in undifferentiated cultures. Using standard and widely accepted methods for reproducible P19 differentiation into all three germ layers, an enhancement of mesoderm and ectoderm differentiation with a concurrent loss of endoderm lineage specification was observed with Y-27632 treatment. Evidence would suggest that this effect is in part mediated through TGF-β and SMAD signaling as ROCK-inhibited cells displayed aberrant SMAD activation and did not return to a ‘ground’ state after the inhibition had been removed. Conclusions/Significance Given this data and the fact that only a partial rescue of normal differentiation capacity occurred when ROCK inhibition was alleviated, the effect of ROCK inhibition on the differentiation capacity of pluripotent cell populations should be further examined to elucidate the role of the Rho-ROCK pathway in early cellular ‘fate’ decision making processes.